Civil Society under Democracy - Ugljesa Radulovic (The Thinker)
During apartheid, the act of disclosing wrongdoing was not a common occurrence in South Africa. With the transition to democratic rule, blowing the whistle on wrongdoing became relatively prominent. However, along with this positive democratic advancement, the South African whistleblower became victim to retaliation. A significant factor contributing to the frequent occurrence of retaliation is the lack of adequate legislative protection for whistleblowers. It is in this context that civil society, which is the voluntary participation of individuals organised around formal and informal associations that are concerned with the advancement of public interests, came forward to support South African whistleblowers. Civil society is, of course, a crucial component for a functional democracy. Nongovernmental organisations form the backbone of civil society. To examine the role of non-governmental organisations in supporting South African whistleblowers, this study employed a qualitative approach. Two qualitative research methods were utilised, namely document analysis which served as the dominant source of data, and semi-structured interviews which were used to supplement the data emerging from the document analysis. The findings indicated that throughout South Africa’s democratic history, non-governmental organisations have advocated for whistleblowers’ rights. They have often aided whistleblowers by providing them legal support, and have made practical tools publicly available to whistleblowers (current and future) to help them better deal with their disclosure experiences. The paper ends with a key recommendation – that non-governmental organisations should better coordinate their efforts to provide whistleblowers more comprehensive support.